Microbiota in the Rhizosphere and Seed of Rice From China, With Reference to Their Transmission and Biogeography - Zhou, Xin; Wang, Jin-Ting; Zhang, Zhi-Feng; Li, Wei; Chen, Wen; Cai, Lei (Frontiers in Microbiology, 2020)
Seeds play key roles in the acquisition of plant pioneer microbiota, including the transmission of microbes from parent plants to offspring. However, seed microbial communities are mostly unknown, especially for their potential origin and factors influencing the structure and composition. In this study, samples of rice seed and rhizosphere were collected from Northeast and Central-south China in two harvest years and analyzed using a metabarcoding approach targeting 16S rRNA region. A higher level of vertical transmission (from parent seed microbiota to offspring) was revealed, as compared to the acquisition from the rhizosphere (25.5% vs. 10.7%). About 3.59% and 7.54% of the seed and rhizosphere OTUs were identified as their respective core microbiota, showing a smaller proposition of core taxa in seed. Among the seed core microbiota, members of bacterial genera like Pantoea, Pseudomonas and Xanthomonas have been reported as important rice pathogens. Both the seed and rhizosphere of rice showed distance-decay of similarity in microbial communities. Seed moisture and WMAT (winter mean annual temperature) had significant impacts on seed microbiota, while WMAT, AK (available kalium), AP (available phosphorus), Al, pH, and TN were the significant variables determining rhizosphere microbiota. By parsing microbial OTUs into function pathways, multiple seed and rhizosphere enriched pathways were characterized, which, to some extent, explained the potential adaptation of seed or rhizosphere microbiota to their living habitats. The results presented here elucidate the composition and possible sources of rice seed microbiota, which is crucial for the health and productivity management in sustainable agriculture.